Illegal evidence in criminal proceedings: Collecting of evidence by authorized officials of internal affairs bodies - Živanović Katarina S. (NBP: Nauka, bezbednost, policija)
The subject of the research is a theoretical, normative and practical analysis of illegal evidence in Serbian law and judicial practice, with a special emphasis on the manner of behaviour of authorized officials of internal affairs bodies, which during the conducting of evidentiary actions can cause the illegality of the obtained evidence. The goal of the research is reflected in the scientific and practical contribution to the scientific and social community, since in addition to the presentation and analysis of prominent scientific and theoretical concepts represented in domestic and foreign literature, the paper contains a detailed presentation of the results of the analysis of domestic courts decisions, but also the decisions of the European Court of Human Rights (ECtHR) in terms of violation of the right to a fair trial (Art. 6 of European Convention on Human Rights). The analysis of the aforementioned court decisions is extremely important, bearing in mind that the institute of illegal evidence de facto represents court standards. Namely, through the analysis of ECtHR decisions, it was established that the court assesses the legality of evidence in light of the violation of the right to a fair trial, in terms of the method of obtaining evidence, causes the unfairness of the procedure (as a whole). By analysing the domestic court practise, it was established in which cases the police collected evidence in an illegal manner, that is, in which cases the evidence was collected in a legal manner.